2022
DOI: 10.3390/pharmaceutics14102141
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antiglycation and Anti-α-Glucosidase Activities of Baicalein, Baicalin (Baicalein 7-O-Glucuronide) and the Antidiabetic Drug Metformin

Abstract: The discovery of new oral antidiabetic drugs remains a priority in medicine. This research aimed to evaluate the activity of the flavonoid baicalein and its natural glucuronide baicalin, compared to the antidiabetic drug metformin, as potential antiglycation, anti–radical, and anti-α–glucosidase agents, in order to assess their potential role in counteracting hyperglycemia-induced tissue damage. The study considered: (i) the BSA assay, to detect the formation of advanced glycation end products (AGEs), (ii) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The findings exhibited that Cu 2+ reducing ability of baicalin hydrate is lower than those that used standard antioxidants. Furthermore, absorbance values for natural phenolic compound have been recorded in the previous literature, including usnic acid's absorbance values for Cu 2+ reduction as 0.277 (r 2 : 0.9836) [53], 0.468 (r 2 : 0.9729) for magnofluorine [28] 0.519 (r 2 : 0.9675) for spiraeoside [57] 0.762 for eugenol (r 2 : 0.9957) [69], 0.780 (r 2 : 0.9981) for coumestrol [16], 1.085 (r 2 : 0.8403) for resveratrol [70], 0.750 (r 2 : 0.9550) for taxifolin [71], and 1.314 (r 2 : 0.9682) for olivetol [72] at the same concentration.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The findings exhibited that Cu 2+ reducing ability of baicalin hydrate is lower than those that used standard antioxidants. Furthermore, absorbance values for natural phenolic compound have been recorded in the previous literature, including usnic acid's absorbance values for Cu 2+ reduction as 0.277 (r 2 : 0.9836) [53], 0.468 (r 2 : 0.9729) for magnofluorine [28] 0.519 (r 2 : 0.9675) for spiraeoside [57] 0.762 for eugenol (r 2 : 0.9957) [69], 0.780 (r 2 : 0.9981) for coumestrol [16], 1.085 (r 2 : 0.8403) for resveratrol [70], 0.750 (r 2 : 0.9550) for taxifolin [71], and 1.314 (r 2 : 0.9682) for olivetol [72] at the same concentration.…”
Section: Discussionmentioning
confidence: 85%
“…The findings demonstrated that baicalin hydrate's Fe 3+ reducing capacity is lower than that of BHA and Trolox but comparable to that of BHT and α-Tocopherol. When examining the literature on this topic, it is observed that the Fe 3+ reducing absorbance for usnic acid has been determined as 0.278 (r 2 : 0.9567) [53], 2.769 for caffeic acid (r 2 : 0.9945) [54], 0.432 (r 2 : 0.9981) for uric acid [55], 0.739 (r 2 : 0.9478) for coumestrol [16], 2.428 (r 2 : 0.9474) for tannic acid [56], 1.012 (r 2 : 0.9523) for spiraeoside [57], 0.967 (r 2 : 0.9938) for magnofluorine [28] and 2.509 (r 2 : 0.9906) for caffeic acid phenethyl ester [58] at similar concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein glycation was obtained in accordance with a previously described method [ 39 , 40 ]. AGEs were detected using BSA (10 mg/mL, pH 7.4) as the protein substrate, and glucose (1.0 M), fructose (0.5 M), or ribose (0.05 M) as glycation inducers.…”
Section: Methodsmentioning
confidence: 99%
“…A study using three structurally related polyphenols, such as baicalin, baicalein and wogonin, showed the inhibition of endothelial cell barrier disruption, suggesting their protective activity against vascular inflammatory diseases [ 75 ]. Recently, studies have suggested that baicalein exhibits potential antidiabetic activities in metabolic syndrome [ 76 ]; the effect is related to the inhibition of α–glucosidase activity [ 77 , 78 ].…”
Section: Specific Polyphenolic Compounds Of Interestmentioning
confidence: 99%